Impact of Green Innovation, Accounting, and Eco-Efficiency on Environmental and Corporate Performance - Mia Audina; Fatchan Achyani; Rina Trisnawati (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the effect of green innovation, green accounting, and eco-efficiency on environmental performance, and analyze its impact on company performance. Methodology: This research uses quantitative methods with descriptive and verification approaches. The data used comes from the financial statements of mining companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2023 period. The analysis techniques used include multiple linear regression analysis and hypothesis testing with SPSS as a tool. Results: The results of the study, it was found that green innovation and green accounting have a significant positive effect on environmental performance. In contrast, eco-efficiency shows a significant negative effect on environmental performance. In addition, environmental performance is also shown to have a significant positive impact on firm performance. Conclusions: This study demonstrates that green innovation and green accounting have a significant positive impact on improving environmental performance. Conversely, eco-efficiency shows a significant negative effect on environmental performance. Furthermore, strong environmental performance positively and significantly contributes to enhancing corporate performance. Therefore, emphasizing green innovation and green accounting is crucial for supporting environmental sustainability while simultaneously improving corporate performance. Limitations: This study only observes mining companies listed on the Indonesia Stock Exchange for 5 years, namely the 2019-2023 period, so this research does not represent the actual conditions of various company sectors. Contribution: These findings support the importance of implementing environmentally friendly practices as part of a strategy to improve company performance in the mining sector.